The Commodification of Islam in Halal Cosmetics Advertising in Indonesia (Judith Williamson Semiotics Analysis) - Mutiah, Isnaini Umi; Andreas, Rino; Mahardika, Dzikrina Aqsha; Setiawan, Azizah Nafabilla; Septiyanti, Nisa Dwi (Universitas Muhammadiyah Surakarta, 2023)
The purpose of this paper is to explain the commodification of Islam in the advertisement of Wardah cosmetic products through Judith Williamson's semiotic analysis. Advertising as a communicative medium aims to influence consumers by constructing the dominant discourse in Muslim society. One of them is seen in Wardah's beauty product advertisement by building Islamic discourse. This qualitative research uses the advertising semiotics method which examines the relation between signifier and signified in an object. The researcher analyzed the scenes in five Wardah advertisements. The results show that